Being at genetic risk toward a rhetoric of care - Pender, Kelly, 1974- (RSA series in transdisciplinary rhetoric., 2018)
"Advocates a conversation around the genetic risk for breast and ovarian cancers that focuses less on choice and more on care. Offers a new set of conceptual starting points for understanding what is at stake with a BRCA diagnosis and what the focus on choice obstructs from view"--Provided by publisher.